Studies on psycho-endocrinology. Current state of knowledge and presentation of 25 clinical cases - Llanos Zuloaga, Roberto (1962)
25 Clinical observations are presented in this paper abstracts from the stories of 10 patients with endocrine-psychiatric symptoms, which corresponded to 12 different endocrinopathies and two acute psychophysiological reactions due to hormone-therapeutic use. Then the findings are discussed and correlated to a previous summary of current knowledge in this field, based on the major publications in the last 10 years and sent to psychopathological aspect of endocrinopathies, endocrine study of mental illness and psychological effects of hormone. The conclusions of psychiatry correlation is established with other specialties and the concept reaffirms the sick man, as a person.